Studi Penempatan Motif Ukiran dan Kaligrafi Islam pada Fasad Masjid Raya Syekh Ahmad Khatib Al Minangkabawi - Rahmat, Miftahul; Heldi, Heldi (TSAQOFAH, 2025)
Masjid Raya Syekh Ahmad Khatib Al-Minangkabawi in West Sumatra is a historic structure that exemplifies the acculturation between Islamic values and Minangkabau local culture. Serving as both a place of worship and a cultural symbol, the mosque features a façade rich in traditional Minangkabau carvings and Islamic calligraphy, each carrying philosophical and religious meaning. This study aims to analyze the placement patterns and visual meanings of the carved motifs and Islamic calligraphy on the façade of the mosque. A descriptive qualitative approach was employed, using literature review and visual analysis. The findings reveal that motifs such as Pucuak Rabuang, Siriah Gadang, Bungo Tanjuang, Kaluak Paku, as well as fauna and anthropomorphic motifs like Motif Bada, Rajo Tigo Selo, and Ninik Mamak, convey moral and social messages such as the pursuit of knowledge, leadership responsibility, and communal harmony. Meanwhile, Islamic calligraphy featuring phrases such as Allah, Muhammad Rasul Allah, and the Shahada (commonly rendered in Thuluth script) is strategically placed to reinforce messages of monotheism and spirituality. These findings demonstrate that the decorative elements serve not only aesthetic purposes but also function as a medium for conveying Islamic values and Minangkabau cultural identity. This research contributes to the preservation of Indonesia’s Islamic cultural heritage and offers valuable insights for developing contextual Islamic architectural design rooted in traditional values.